2014
DOI: 10.3126/eco.v19i0.9848
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Seed Germination Behaviour in Phyllanthus Amarus by Acid and Mechanical Scarification Pretreatments

Abstract: Phyllanthus amarus (Bhui-Aanwalaa: Family: Euphorbiaceae) is considered to be the most important medicinal plant of the Indian Thar desert. The present article deals with its seed morphological parameters, seed output, reproductive capacity (RC), germination behavior, seedling growth, root: shoot ratio (R/S ratio), germination value (GV) and vigour index (VI) in fresh and one-year-old seeds under controlled laboratory conditions. Results revealed that 73.33 and 60% germination was observed in fresh and one-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The variations in the value of germination were numerically highly significant at a significance level of 0.05, because of stirring the blender for 4 minutes which gave the greatest value in peak value character which did not significantly differ with a blender stirring of 2 minutes for the mean daily germination value which caused the highest value. Gehlot and Kasera (2012) reported that the highest germination value was achieved in mechanical and concentrated H2SO4 scarification process for 2 min. Salvi et al (2015) stated that the pre-treated seed with scarification process performed better in respect to germination value in comparison with other treatments.…”
Section: Germination Valuementioning
confidence: 99%
“…The variations in the value of germination were numerically highly significant at a significance level of 0.05, because of stirring the blender for 4 minutes which gave the greatest value in peak value character which did not significantly differ with a blender stirring of 2 minutes for the mean daily germination value which caused the highest value. Gehlot and Kasera (2012) reported that the highest germination value was achieved in mechanical and concentrated H2SO4 scarification process for 2 min. Salvi et al (2015) stated that the pre-treated seed with scarification process performed better in respect to germination value in comparison with other treatments.…”
Section: Germination Valuementioning
confidence: 99%